Implementation of Collaborative Governance in Countering Terrorism in Indonesia - Muhammad Syauqi Khudzaifi; Petrus Polyando; Frans Dione (Jurnal Indonesia Sosial Teknologi, 2024)
Terrorism is one of the global threats that can affect Indonesia's social, political, and economic stability. Currently, terrorism has been categorized as an extraordinary crime that requires extraordinary efforts from various parties to counter it. This research examines and describes the collaboration process built into countering terrorism in Indonesia. This research uses a descriptive qualitative method with six informants as research subjects. The results show that implementing collaborative governance to counter-terrorism in Indonesia has been running well and involves many parties. However, in the context of the stages of the implementation of collaboration, there are still obstacles. The motivational factor of the parties involved in counterterrorism is enough to influence the imbalance of resources and knowledge among collaborative actors. Different perceptions in addressing the issue of terrorism have caused the starting conditions in the implementation of collaboration not to work properly. This affects the commitment between collaboration actors and the consistency in running various terrorism prevention programs. In addition, the lack of strong regulations governing BNPT's role as coordinator in terrorism prevention causes obstacles in the synergy process. Collaboration has been implemented in terms of quantity, but in terms of quality, there are still things that are not optimal.